Effect of Flow Rate of Side-Type Orifice Intake on Withdrawn Water Temperature. (11th June 2014) - Gao, Xueping; Li, Guangning; Han, Yunpeng
Abstract : Side-type orifice intake is a type of selective withdrawal facility used in managing reservoirs to mitigate the negative effects of low-temperature water. Based on the temperature data of a thermal stratified reservoir in China, an experiment was conducted in flume to study the influence of intake flow rate on withdrawn water temperature with different temperature distributions. Results indicated that withdrawn water temperature changed with different flow rates. The temperature change was determined by the water temperature gradients above and below the intake, whereas the change trend of temperature depended on the difference between the water temperature gradient above and below the intake. We likewise proposed a new equation with which the withdrawn water temperature of a thermal stratified reservoir using a side-type orifice could be calculated. These findings could be directly applied to the design and operation of side-type orifice intake in thermal stratified reservoirs.